THE EFFECT OF EDUCATION LEVEL, WORK EXPERIENCE, AND EMPLOYEE AGE ON EMPLOYEE PERFORMANCE AT RESTU BUNDA COFFEE SHOP MEDAN - Dimas Arya Nugraha; Syahratun Nazrah; Rizkia Nur Yasinta; M. Fadhlan Mirza; Deni Faisal Mirza (RADJA PUBLIKA, 2025)
Employee performance is a crucial factor in determining a company's success in achieving organizational goals. In practice, various individual factors, such as education level, work experience, and employee age, are often assumed to influence employee performance at Restu Bunda Coffee Shop Medan, both partially and simultaneously. The approach used was a quantitative approach with a survey method. The sampling technique was random sampling, with data collected through distributing questionnaires to employees as respondents. The data obtained were analyzed using multiple linear regression methods. This analysis process was carried out with the help of SPSS version 30 software. The results of this study show that, partially and simultaneously, the variables of education level, work experience, and age do not have a significant influence on employee performance. This finding influence on employee performance. This finding indicates that these three factors are not the main determinants in improving employee performance at Restu Bunda Coffee Shop Medan. Therefore, companies are advised to examine more related factors such as work motivation, stress load, discipline, and work environment in an effort to optimize employee performance.